The identification of mentally retarded children in the Division of City School Manila - Montaña, Patricia Martinez 1922- (College of Education, University of the Philippines Diliman, 1968)
The aim of the study is to determine who the mentally retarded children are, and how the mentally retarded children are identified in elementary public schools in Manila. The major purpose of the study is to present some methods of identifying mentally retarded children in the Division of City Schools in Manila. Because basic the special education program for the mentally retarded is the need for efficient and reliable methods of identifying mentally retarded children.